GENDERED OPPRESSION IN THE FILM MAI (2024): AN ANALYSIS OF RESISTANCE STRATEGIES THROUGH YOUNG'S FIVE FACES OF OPPRESSION - Anggraeni, Ines Vike Nur (Universitas Negeri Surabaya, 2026)
Throughout history, women have persistently encountered inequity within patriarchal cultures. This study examines gender oppression portrayed in the Vietnamese film Mai (2024), directed by Trấn Thành. Employing Iris Marion Young's Five Faces of Oppression theory (1990), this research analyzes Mai's experiences of gender oppression as a woman in a patriarchal culture, particularly in her role as a widow. The study identifies three of the five forms of oppression encountered by Mai: exploitation, marginalization, and violence, as outlined in Young's oppression theory. Through a visual narrative approach, the findings demonstrate that women who experience gender oppression do not remain passive. Through Mai's character, this research establishes that oppressed women possess the capacity to voice resistance through initiating new romantic relationships, severing toxic family ties, and opening new chapters in their lives by pursuing their aspirations as independent women.